2010
DOI: 10.1080/02772240902810419
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in plasma electrolyte levels of a freshwater fishCyprinus carpioexposed to acidic pH

Abstract: The impact of acidification (Low pH 5.0) on plasma electrolytes (Na þ , K þ , Cl À , Ca 2þ , and Mg 2þ ) in a freshwater fish Cyprinus carpio was studied for a 35 day (long term) exposure period, while control groups were maintained at neutral pH (7.3). During long-term (35 days) exposure periods, plasma K þ and Mg 2þ levels were increased (77.8% and 16.0%) in the low pH (5.0) treated fish. On the other hand, plasma Na þ , Cl À , and Ca 2þ levels were decreased (12.4%, 18.4% and 31.3%, respectively). The loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The impairment of osmoregulatory mechanisms by ammonia may be associated with the inhibition of ATPase activity (Wang, Wang, Wang, Shang, Liu & Suna ). In freshwater organisms, the enzyme Na + /K + ‐ATPase located at the basolateral membrane of gill epithelial cells plays a major role in the maintenance of ion balance and subsequent osmoregulation (Mathan, Kurunthachalam & Priya ). To maintain ammonia homeostasis Na + /K + ‐ATPase activity may engage the exchange of sodium from the water for ammonia in the fish (Randall & Tsui ; Alam & Frankel ).…”
Section: Resultsmentioning
confidence: 99%
“…The impairment of osmoregulatory mechanisms by ammonia may be associated with the inhibition of ATPase activity (Wang, Wang, Wang, Shang, Liu & Suna ). In freshwater organisms, the enzyme Na + /K + ‐ATPase located at the basolateral membrane of gill epithelial cells plays a major role in the maintenance of ion balance and subsequent osmoregulation (Mathan, Kurunthachalam & Priya ). To maintain ammonia homeostasis Na + /K + ‐ATPase activity may engage the exchange of sodium from the water for ammonia in the fish (Randall & Tsui ; Alam & Frankel ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, high H + disrupt the tight junctions of gill epithelia causing greater ionic loss by paracelullar route (KUMAI et al, 2011;KWONG & PERRY, 2013), and the net H + excretion by the H + -ATPase observed in neutral waters is reduced (BRIX et al, 2013). Higher plasma K+ levels after exposure to acidic pH (pH 5.0) was also observed in common carp (MATHAN et al, 2010). These authors supposed that this elevation is due to intracellular K + release from muscles as H + enters.…”
Section: Discussionmentioning
confidence: 97%
“…The effects of toxicants on osmotic and ionic regulation have been calculated by means of measuring concentrations of individual ions and total osmolarity in fish plasma (Barcarolli and Martinez, 2004). Mathan et al (2010) reported that alterations in ionic balance may be due to due to stress effects on the ionoregulatory organs. McCarty and Houstan (1976) reported that the decrease in plasma electrolyte levels tend to be associated with increases in tissue concentration, particularly sodium and chloride.…”
Section: Gpt Activity (Iumentioning
confidence: 99%